2009
DOI: 10.1590/s0100-736x2009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular diastolic echocardiographic parameters in healthy dogs by pulsed-wave Doppler

Abstract: Left ventricular diastolic dysfunction plays an important role on heart failure progression. In order to obtain additional reference values of left ventricular diastolic parameters and investigate influence of common variables, peak E wave (peak E), peak A wave (peak A), E/A ratio (E/A), E wave deceleration time (EDT) and isovolumic relaxation time (IRVT) were studied in 40 clinically healthy dogs, by pulsed wave Doppler. The following values were obtained: peak E = 0.747 ± 0.117 m/s, peak A = 0.487 ± 0.062 m/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Although no data regarding mitral peak velocity was found in the literature, the velocities of transmitral peak early (E) and transmitral peak late (A) diastole are identical to those found by Pereira et al (2009) and similar to those described in German Shepherd dogs by Muzzi et al (2006) and Schober & Fuentes (2001). An E/A ratio greater than 1 and less than 2 indicates a normal relaxation pattern, as seen in this case.…”
Section: Discussionsupporting
confidence: 82%
“…Although no data regarding mitral peak velocity was found in the literature, the velocities of transmitral peak early (E) and transmitral peak late (A) diastole are identical to those found by Pereira et al (2009) and similar to those described in German Shepherd dogs by Muzzi et al (2006) and Schober & Fuentes (2001). An E/A ratio greater than 1 and less than 2 indicates a normal relaxation pattern, as seen in this case.…”
Section: Discussionsupporting
confidence: 82%
“…45,46,47 Human and canine studies report a decrease in the E':A' ratio with advancing age. 48,49,50 In humans, this condition is linked to a decline in diastolic functions of the heart as one grows older. 51 Similarly, we found a decrease in the E':A' ratio in conjunction with increasing age and a moderate negative correlation between age and the E':A' ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight correlated significantly (r=0.42) with IVRT, in line with findings of O' Sullivan et al (2007) but contrary to findings of Bodh et al, (2020). Fast heart rate in small sized dogs cause early left ventricular filling resulting in premature opening of mitral leaflets and thus shortening of IVRT (Pereira et al, 2009). The duration of E-wave was greater than normal dogs (Schober et al, 1998) and the duration of A-wave was also greater than values reported previously (Schober et al, 1998;O'Sullivan et al, 2007 andBodh et al, 2020).…”
Section: Resultsmentioning
confidence: 78%
“…Studies on Pulsed-wave Doppler Echocardiographic Parameters of Blood Flow through Mitral, Tricuspid and Aortic... of Pereira et al (2009) and Bodh et al (2020), but contrary to findings of O'Sullivan et al (2007) in Doberman Pinschers where majority of Doppler echocardiographic variables correlated significantly with body weight. Time interval from peak to end of mitral E-wave represented mitral deceleration time (DT E ).Value in Indian Spitz were lower than German Shepherd (Muzzi et al, 2006), Doberman Pinscher (O' Sullivan et al, 2007 and Indian mongrel dogs (Bodh et al, 2020).Mitral DT E correlated nonsignificantly with gender and body weight similar to findings in Indian mongrel dogs (Bodh et al, 2020).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation